Struktury heterarchiczne w administracji publicznej - Chrisidu-Budnik, Agnieszka (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The purpose of this article is to present heterarchy structures. This structures are becoming increasingly important in process of realization public services. This paper outlines the specificity of relational contracts as well as the role of trust in collaborative relationships. It presents the evolution of governance.
Keywords: relational contracts; heterarchy; trust; governance